AB1188 AUDIT: IMPACT OF MUSCULOSKELETAL ULTRASOUND USE IN RHEUMATOLOGY CLINICS. (June 2019) - Wilkinson, Andrew; Reed, Mike; Else, Sara
Abstract : Background: Musculoskeletal ultrasound (MSUS) has assumed a prominent role in rheumatological practice as both a diagnostic and monitoring tool. 1 It has utility in excluding and quantifying active synovitis and can be used to guide adjustments of therapies. 2, 3 Objectives: We aimed to observe impacts on clinical practice of utilising ultrasound (US) scanners in outpatient clinics in a district general rheumatology service. We were particularly interested to see if this affected treatment choices, follow-up plans and referrals for radiological investigations. Methods: US scanners were obtained and used by 2 rheumatology consultants with previous ultrasound training. Scanning was performed during standard 20 minute appointments within general rheumatology outpatient clinics. No extra time was allocated. Over 8 weeks, we completed questionnaires for each scan and assessed the impact on management decisions. Results: Over 8 weeks, data was collected for 36 consecutive patients scanned. Commonly imaged joints were hands (81%, n=29), wrists (75%, n=27), feet (19%, n=7), and ankles (14%, n=5). Most common patient diagnoses were osteoarthritis (n=13, 36%), rheumatoid arthritis (n=10, 28%) and psoriatic arthropathy (n=6, 17%). The remaining patients had diagnostic labels including undifferentiated inflammatory arthritis or no formal diagnosis. Abnormalities suggesting active inflammation were seen in 42%. In 33% osteoarthritic changes were observed, erosions were seen in 5%. 20% scans were normal. US altered the management in 58% (n=21/36) of cases. These alterations to management included: drug added(n=5), drug stopped(n=3), dose increase (n=1), joint injection (n=3), intramuscular injection (n=2). Of the medications added, 3 were DMARDs, 1 was a biologic therapy and one case was not specified. The medications stopped were all DMARDS. US use in clinic prevented radiological investigation in 72% (26/36) of cases. These were radiology ultrasound (n=23) and MRI (n=3). Hands and wrists scans accounted for 86% of these. US altered the follow up in 56% (20/36) of cases. Of these, 40% (8/20) were reviewed earlier, and 40% (8/20) of patients were discharged based on ultrasound information. In 16/36 patients, US did not alter management. The average time taken to scan in clinic was 7 minutes per patient. The median time was 5 minutes, with the average skewed due to a few prolonged scans of multiple anatomical areas. Conclusion: This audit has demonstrated that US use has impacted on our clinical practice. We identified patients to be seen earlier and altered management based on US findings. US use also prevented radiological investigations in 72% of cases. This has positive impacts on staffing, finances, radiology department capacity and patient convenience. Furthermore, we were able to discharge 40% of patients who otherwise would have been recalled. Overall, we believe this audit shows positive impacts of MSUS on patient care. Challenges include time pressures of scanning in clinic, time and cost implications of ultrasound training and the need to standardise and record ultrasound methods and findings consistently. Costs are offset by savings to radiology resources and increased discharges. We plan to expand ultrasound usage and train our colleagues to employ ultrasound for our patients. References: [1] Möller I, Janta I, Backhaus M, et al. The 2017 EULAR standardised procedures for ultrasound imaging in rheumatology Annals of the Rheumatic Diseases 2017;76:1974-1979. [2] Alivernini S, et al. Tapering and discontinuation of TNF-alpha blockers without disease relapse using ultrasonography as a tool to identify patients with rheumatoid arthritis in clinical and histological remission. Arthritis Res Ther18:39. [3] Bawa S, Todd M, France J SAT0203 Optimization of biologic tapering using ultrasound in ra patients Annals of the Rheumatic Diseases 2018;77:962. Disclosure of Interests: Andrew Wilkinson: None declared, Mike Reed Speakers bureau: Paid to speak at meeting by Novartis, Sara Else Consultant for: Contributed to advisory boards for: Abbvie, Norartis, Roche and Chungai Pharma., Speakers bureau: Paid to organise and chair meetings, and speak at educational events by following companies: BMS, Celegene, Grifols, Jansess, MSD, Novartis, UCB.